Various Technical Variables in Blanching, Coating, Frying to the Physicochemical Properties Fried Pigmented Potato (solanum tuberosum l.) Crisp - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
Pigmented potato (Solanum tuberosum L.) varieties are a rich source of anthocyanins, in particular acylated derivatives. The potato products such as French fries, chips, balls etc. are also fried products which absorb high amount of oil. These products though taste good, pose health problems due to high calorie and cholesterol intake. The consumers prefer to low fat and fatfree fried foods. This research has been focused on different parameters of blanching, coating, frying, kind of frying oil for minimum oil absorption and sensory palatability while maintaining the most phytochemical components such as total phenolic, total flavonoid and anthocyanin during preservation. Results revealed that blanching 95oC in 30 seconds with ascorbic acid of 0.05 g/100g potato, coating with carrageenan 0.20%, frying 4 mm of potato crisp in sunflower oil heating at 155oC in 2 minutes was appropriated. Fried potato crisp could be preserved for 12 weeks at ambient 4oC. Moisture and oil content, as well as colour and texture are important quality attributes of fried potato products which were significantly affected by blanching. Reducing the oil content of fried potato slices by application of coating is an effective method. Frying of potato crisps is carried out to convert the tubers to value added products. Frying method brings out unique flavor and texture to the products that improve their overall acceptability. Kind of oil used for frying also positively affected to oxidative reaction in fried potato crisps. The present study has examined various technical aspects to minimize the oil uptake in fried foods still retaining the desirable texture and flavor of the final product.Keywords: Potato crisp, Blanching, Coating, Frying, Shelf life, Anthocyanin, Flavonoid, Carrageenan.